ChemInform Abstract: Bismuth Acetate as a Catalyst for the Sequential Protodeboronation of Di‐ and Triborylated Indoles. Issue 33 (July 2016) - Shen, Fangyi; Tyagarajan, Sriram; Perera, Damith; Krska, Shane W.; Maligres, Peter E.; Smith, Milton R.; Maleczka, Robert E. Jr.
Abstract: An iridium‐catalyzed preparation of mono‐, di‐ and triborylated indole derivatives followed by bismuth‐ or iridium‐catalyzed protodeborylation is described which allows for the regioselective synthesis of 4‐, 5‐ or 7‐monoborylated, 2, 7‐, 4, 7‐ and 3, 5‐diborylated as well as 2, 4, 7‐triborylated indole derivatives.